UPACARA TETEK PANTAN DI KABUPATEN KOTAWARINGIN TIMUR - -- Sulandra (Dharma Duta, 2019)
Ritual is a very important thing for Dayak people. If done sincerely, rituals can increase motivation and life balance. Of the many rituals, Dayak people have a ritual called Pantan. Tetek Pantan is a welcome ritual to the honor guest. Pantan can be interpreted as a barrier tree. In the implementation of the ritual, the Pantan is cut as a sign of the guest has been well received. Potong Pantan or Tetek Pantan ritual is cutting, dispelling nightmares, distractions and obstacles. Thus, guests will be protected from God, Health, Longevity, and success